The Effects of Ethics Institutionalization on Organizational Citizenship Behavior: The Mediating Effects of Organizational Commitment and Moderating Effects of Psychological Empowerment - Destika Sandakila , Eka; Satrya, Aryana (KnE Social Sciences, 2020)
Many of organization implement code of conduct as an explicit guidance to help employees knowing the standard of ethics from management“s viewpoints, with the aim to gain productivity achieving organization“s goal. The purpose of this paper is to examine the influence of ethics institutionalization on organizational citizenship behavior and to analyze the role of organizational commitment in mediating the impact of ethics institutionalization on organizational citizenship behavior with psychological empowerment as a moderator in one of State Institution in Indonesia. This research will use a quantitative approach with online survey method to 250 respondents which were determined by purposive sampling method. Respondents come from employees of XYZ State Institution who already work at the institution for minimum 2 years. Based on analysis from preliminary literature, it can be concluded that all variables used in this research are valid, reliable and having correlation with each others. This research is still on progress and result will be discussed further. Keywords: Institutionalization of Ethics, Explicit Ethics Institutionalization, Implicit Ethics Institutionalization, Organizational Commitment, Psychological Empowerment, Organizational Citizenship Behavior